Hasil Tindakan Bedah Implantasi Glaucoma Drainage Device pada Pasien Glaukoma Refrakter di RSUP dr Sardjito - Saputra, Yuandani; Jati, Krisna Dwi Purnomo; Gani, Tatang Talka; Ekantini, Retno (Majalah Oftalmologi Indonesia, 2023)
Introduction: Glaucoma drainage device (GDD) implantation was an effective surgical procedure in treating uncontrolled intraocular pressure (IOP) of glaucoma patients in certain complicated conditions. GDD implants were classified into valved and non-valved in which its surgical outcomes in different types of device and various etiologies were not similar. This study aimed to evaluate the surgery outcomes of GDD implantation in patients with refractory glaucoma at Sardjito General Hospital. Methods: All 12 eyes of 11 patient’s medical records who underwent GDD implantation during 2022 at Sardjito General Hospital was reviewed. Baseline data include age, gender, eye laterality, type of glaucoma, IOP and visual acuity. The IOP and visual acuity (LogMAR) were measured at week 1, month 1, 2 and 3. Type of GDD implants, postoperative glaucoma medications, complications and need for further glaucoma surgery were documented. Results: The mean IOP at baseline was 44 ± 14.2 mmHg with 3.4 ± 0.6 glaucoma medications. It decreased after surgery into 19.1 ± 11.2 mmHg (p=0.003) at 3 months follow up with 0.7 ± 1.7 (p=0.002) glaucoma medications. The mean initial visual acuity was 1.9 ± 0.6 and changed insignificantly to 1.7 ± 0.8 (p=0.624) at last follow up. Six eyes (50%) were implanted with valved implant. The most common early postoperative complications were recurrent high IOP (4 eyes, 33.3%) associated to ripcord of non-valved implant (p=0.025). Five eyes (41.7%) needed additional surgery related to non-valved implant type (p=0.003). Conclusion: GDD implantation especially valved type appears to be safe and effective surgical option in treating refractory glaucoma patients Keywords: Glaucoma drainage device, refractory glaucoma, glaucoma surgery, intraocular pressure